2012
DOI: 10.1590/s1981-67232012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Pulp yield and mineral content of commercial hybrids of yellow passion fruits

Abstract: SummaryPhysical analyses and an analysis of the mineral content were carried out by peroxide-perchloric wet-digestion, taking readings using inductively coupled plasma-atomic emission spectrometry (ICP-AES) and measurements using an analytical balance and digital paquimeter, of three commercial hybrids of Passiflora edulis f. flavicarpa Deg.: BRS Sol do Cerrado, BRS Ouro Vermelho and BRS Gigante Amarelo, cultivated and harvested from the experimental area of Embrapa Cerrados, Planaltina, DF, Brazil, in October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The studies of Campos et al (2010) and Miele et al (2015) showed similar iron and zinc contents to our grape PSDs, once we obtained 6.2 mg.L -1 of Zn and 2.0-11.4 mg.L -1 of Fe. Among commercial hybrids of passion fruit, Tupinambá et al (2012) reported a maximum iron similar to the concentration analyzed in the grape flavor of brand C, but lower to the other samples, and zinc was lower than ours. Orisakwe et al (2009) obtained lower concentration of zinc in a grape juice, while Ackha et al ( 2014) obtained mean concentrations of iron and zinc also lower than this study.…”
Section: Determination Of Iron and Zinc In Powdered Soft Drinkssupporting
confidence: 45%
“…The studies of Campos et al (2010) and Miele et al (2015) showed similar iron and zinc contents to our grape PSDs, once we obtained 6.2 mg.L -1 of Zn and 2.0-11.4 mg.L -1 of Fe. Among commercial hybrids of passion fruit, Tupinambá et al (2012) reported a maximum iron similar to the concentration analyzed in the grape flavor of brand C, but lower to the other samples, and zinc was lower than ours. Orisakwe et al (2009) obtained lower concentration of zinc in a grape juice, while Ackha et al ( 2014) obtained mean concentrations of iron and zinc also lower than this study.…”
Section: Determination Of Iron and Zinc In Powdered Soft Drinkssupporting
confidence: 45%
“…Its fruits are large and can be destined for industry and table, oblong shape, bright yellow color, with mass ranging from 150 g to 350 g, length from 7.7 cm to 9.4 cm, diameter from 7.0 cm to 8.4 cm and thickness of the bark on average of 6.9 mm which ensures resistance to transport, in addition to longer shelf life (Krause et al, 2012;Tupinambá et al, 2012). The pulp, of strong yellow coloration, presents a higher amount of vitamin C, soluble solids from 13 ºBrix to 14 ºBrix, acidity and pH on average 4.5% and 2.9%, with pulp yield ranging from 35% to 40% depending mainly on the performance of artificial pollination (EMBRAPA, 2014b;Andrade Neto et al, 2015b).…”
Section: Brs Sc1mentioning
confidence: 99%